2020
DOI: 10.3390/w12061621
|View full text |Cite
|
Sign up to set email alerts
|

The Mixing Regime and Turbidity of Lake Banyoles (NE Spain): Response to Climate Change

Abstract: This study analyses the water temperature changes in Lake Banyoles over the past four decades. Lake Banyoles, Spain’s second highest lake, situated in the western Mediterranean (NE Iberian Peninsula). Over the past 44 years, the warming trend of the lake’s surface waters (0.52 °C decade−1) and the cooling trend of its deep waters (−0.66 °C decade−1) during summer (July–September) have resulted in an increased degree of stratification. Furthermore, the stratification period is currently double that of the 1970s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…For example, in Lobo reservoir [43] it was observed that maximum particulate and organic matter resuspension is caused by turbulence on days of high wind speed. In reference [44] it is said that the turbidity of the surface layer is attributed to the decrease in incoming water caused by the decrease in rainfall, which, in turn, causes a decrease in the buoyancy of the hydrothermal plumes. In addition, it could cause a reduction in the supply of sediment from runoff.…”
Section: Water Clarity and Meteorological Conditionsmentioning
confidence: 99%
“…For example, in Lobo reservoir [43] it was observed that maximum particulate and organic matter resuspension is caused by turbulence on days of high wind speed. In reference [44] it is said that the turbidity of the surface layer is attributed to the decrease in incoming water caused by the decrease in rainfall, which, in turn, causes a decrease in the buoyancy of the hydrothermal plumes. In addition, it could cause a reduction in the supply of sediment from runoff.…”
Section: Water Clarity and Meteorological Conditionsmentioning
confidence: 99%
“…The groundwater turbidity is caused by modifications of the rainfall regime which, over the years, have worsened due to climate change (Sappa et al 2018;Serra 2020), and are accordingly associated with a decrease in springs flow rates caused by the cyclical rainfall reduction (Fig. 2).…”
Section: Inroductionmentioning
confidence: 99%